Analysis of the Influence of Risk Perception, Customer Testimonials and Shopping Experience on COD Purchase Decisions on the Shopee Platform - Susipta, I Nyoman; Purnomo, Muhammad Jefry; Pakaja, Fachrudin (International Journal of Economics and Business Management, 2025)
Online shopping has become an activity that is of interest to most Indonesians in recent years. With the Shopee platform, people can shop from home. However, in its application there are still many weaknesses in purchasing decisions. Therefore, this study aims to analyze the influence of risk perception, customer testimonials, and shopping experience on COD purchasing decisions on the Shopee platform. A quantitative approach was carried out on data sources totaling 303 respondents who will be analyzed using SEM analysis. The results of the study showed that risk perception had no significant effect on purchasing decisions, while customer testimonials and shopping experience had a significant effect on purchasing decisions. Risk perception, customer testimonials, and shopping experience together had a moderate effect on COD purchasing decisions on the Shopee platform.